Improvement of Mechanical Properties for Electrical Conductive Polymer Composites - Hussein, Samah Mohammed (Al-Nahrain Journal of Science, 2016)
Polyaniline (PANI) has been studied extensively as a conducting polymer because of its environmental stability. However, its applications are limited because of its poor mechanical properties. The goal of this study is to improve mechanical properties whilst still retaining electrical conductivity The method was applied for preparing the conductive PANI composites by deposition of the PANI on the prepared composites (UPE / glass fiber) and (UPE / Kevlar fiber). The chemical oxidative method was adopted for polymerization of the aniline and simultaneously protonated of PANI with a hydrochloric acid at concentration (1M). The used oxidation agent is Hexahydrate Ferric Chloride (FeCl3.6H2O). The conductivity results indicated the prepared composites lie within semiconductors region and continuous increase unless after immersed it in the preparing solution after 8weeks.The mechanical properties (bending, hardness) were studied, and also estimated as a function of water and preparing solution absorption with submersion time at room temperature for a period up to 8weeks. The obtained results showed to be increase for both properties unless after continuously immersion despite to be responded to the immersion. These results no affected on the conductivity results.